The structure of the Aramaic treaties of Sefire - Van Rooy, H. F. (Journal for semitics, 1989)
The problem of the structure of the Aramaic treaties of Sefire remains unanswered in existing studies dealing with these treaties. This paper submits a hypothesis constructed on especially the content and placement of I Sefire C and II Sefire C and the design of III Sefire. The probable structure of these treaties is: introduction, list of gods, curses, document clause and stipulations.